Macroeconomic and Firm Specific Factors Affecting Stock Market Liquidity in Nepal - Kushwaha, Aashish; Kunwar, Ajay; Shah, Anuradha Kumari; Chhetri, Arati Thapa; Mishra, Ashmita; Kapri, Asmita; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2025)
This study examines the macroeconomic and firm-specific factors affecting stock market liquidity in Nepal. Turnover ratio and illiquidity ratio are selected as the dependent variables. The selected independent variables are firm size, earnings per share, GDP growth rate, inflation rate, interest rate and leverage. The study is based on secondary data of 12 commercial banks with 120 observations for the period from 2014/15 to 2023/24. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of the macroeconomic and firm-specific factors affecting stock market liquidity in Nepal. The study showed that firm size has a positive impact on illiquidity ratio and turnover ratio. It indicates that larger the firm size, higher would be the illiquidity ratio and turnover ratio. Similarly, earning per share has a positive impact on illiquidity ratio and turnover ratio. It indicates that increase in earnings per share leads to increase in illiquidity ratio and turnover ratio. However, inflation rate has a negative impact on illiquidity ratio and turnover ratio. It indicates that increase in inflation rate leads to decrease in illiquidity ratio and turnover ratio. Likewise, interest rate has a negative impact on illiquidity ratio and turnover ratio. It indicates that increase in interest rate leads to decrease in illiquidity ratio and turnover ratio. In contrast, GDP growth rate has a positive impact on illiquidity ratio and turnover ratio. It indicates that higher the GDP growth rate, higher would be the illiquidity ratio and turnover ratio. However, leverage has a negative impact on liquidity ratio and turnover ratio. It indicates that increase in leverage leads to decrease in illiquidity ratio and turnover ratio.